METHOD OF THE DETACHED LEAF TO EVALUATE RESISTANCE OF THE SOYBEAN TO OÍDIUM - KAMIKOGA, Aurea Tomoko Matsumoto (Scientia Agraria, 2002)
The soybean Powdery Mildew caused by Microsphaera diffusa Cooke & Perk has been causing sporadic losses in Brazil, estimated around 40% at the 96/97 crop season. The potential risk represented by this disease for the soybean crop justifies studies that allow us to know more about the epidemiology of this pathogen in our country. The Modified Detached Leaf Method (MFDM), carried out in vitro in the laboratory, was just as efficient as the tests carried out in the greenhouse or at the field to evaluate the resistance of 10 soybean cultivars. In these tests the cultivars FT - 10, FT - 5, IAC - 100 and MG/BR - 46 (Conquista) were resistant to the pathogen, BRS 133 and FT - Jatobá were moderately resistant, EMBRAPA - 48 was susceptible and BR - 16, FT - Estrela and Coodetec 201 were highly susceptible. With the MFDM, the more suitable foliar stages for the inoculation were the V1, V2 and the V3 due to presenting more vitality, survival and root taking. The inoculum concentration of 1.5 x 107 and 1.5 x 108 were more eficient and as an inoculation method, the spraying method presented a better performance when compared to the pipeting and the sprinkle method. From a total of 52 species of plants from the weed inoculated at the green house with the pathogen, 3 new hosts were observed: Galinsoga parviflora, Physalis angulata e Sonchus oleraceus, not to mention the confirmation of others already reported in different countries and in Brazil. The frequence of plants from the weed at the soybean crop fields, other then representing an inoculum source in the crop season, may be responsible for the pathogen maintenance between the harvest period. The frequence of plants from the weed at the soybean crop fields, other then representing an inoculum source in the crop season, may be responsible for the pathogen maintenance between the harvest period. During this research the presence of the sexual phase of the fungi was not observed, even in laboratory conditions, when the natural environmental conditions were manipulated, even in the commercial fields surveys carried out in Paraná State and Goiás State.